Consumer optimism and price discrimination - Kfir Eliaz; Ran Spiegler (Theoretical Economics, 2008)
We study monopolistic design of a menu of non-linear tariffs when consumers have biased prior beliefs regarding their future preferences. In our model, consumers are "optimistic'' if their prior belief assigns too much weight to states of nature characterized by large gains from trade. A consumer's degree of optimism is his private information, and the monopolist employs the menu of non-linear tariffs to screen it. We characterize the optimal menu and show that the existence of non-common priors has significant qualitative implications for price discrimination and ex-post inefficiency. Finally, the characterization enables us to interpret aspects of real-life menus of non-linear tariffs.
Keywords: D42; D84; D86; 330; contracts; speculative trade; screening; non-common priors; mechanism-design; optimism; three-part tariffs